Are There More Female Managers in the Retail Sector? Evidence from Survey Data in Developing Countries - Amin, Mohammad; Islam, Asif (World Bank, Washington, DC, 2014)
This paper uses firm-level data for 87 developing countries to analyze how the likelihood of a firm having female vs. male top manager varies across sectors. The service sector is often considered to be more favorable toward women compared with men vis-à-vis the manufacturing sector. Although the exploration of the data confirms a significantly higher presence of female managers in services vs. manufacturing, the finding is entirely driven by retail firms, with little contribution from other service sectors, such as wholesale, construction, and other services. The analysis also finds that the higher presence of female managers in the retail sector vs. manufacturing is much higher among the relatively small firms and firms located in the relatively small cities. These findings could serve as useful inputs for the design of optimal policy measures aimed at promoting gender equality in a country.